AMBIGUITY AND AMBIVALENCE AS STRUCTURAL PRINCIPLES - Sarma R. , Lalitha; C. Patel, Rajeshwari (Journal of Dharma, 2016)
There is ambivalence and lack of finality in the structure of texts with representation of women. This paper studies the ambiguity of character delineation and ambivalence in the structure of feminist texts using Doris Lessing’s The Golden Notebook as an alibi. The ambiguity and ambivalence in The Golden Notebook is intended, deliberate and consciously artistic. The incommensurability of woman’s experiences, her variety and contrariness, demand and deserve a higher order of conscious artistry. Ambiguity, as in the dilation of boundaries in the self, is, therefore, ineluctably intertwined with ambivalence in the form of texts that negotiates gender as a category of perception.